1, 25‐Dihydroxyvitamin D3 Inhibits Nuclear Factor Kappa B Activation by Stabilizing Inhibitor IκBα via mRNA Stability and Reduced Phosphorylation in Passively Sensitized Human Airway Smooth Muscle Cells. (24th January 2013) - Song, Y.; Hong, J.; Liu, D.; Lin, Q.; Lai, G.
Abstract Excessive activation of nuclear transcription factor‐κB (NF‐κB) is involved in human airway smooth muscle cells (HASMCs) activities in asthma. We investigated the effects of 1, 25 – dihydroxyvitamin D3 [1, 25 – (OH) 2D3] on the NF‐ κB signaling pathway in passively sensitized HASMCs and the molecular mechanisms involved. HASMCs were treated with either healthy controls' serum, asthma patients' serum or pretreated with 1, 25 – (OH) 2D3 prior to treatment with asthmatics' serum. At 1 h after serum treatment: electrophoretic mobility shift assay (EMSA) was used to detect NF‐κB DNA binding activity; immunocytochemical staining was used to observe the nuclear translocation of NF‐κB p65; Western blots were used for NF‐κB p65, IκBα, and phospho‐IκBα protein levels and the nuclear translocation of NF‐κB p65; real‐time quantitative PCR was used for NF‐κB p65 and IκBα mRNA expressions; and actinomycin D treatment was used to determine IκBα mRNA stability. Our major findings were: (1) 1, 25 – (OH) 2D3 significantly reduced asthma serum passively sensitized HASMCs NF‐κB DNA binding activity and inhibited the nuclear translocation of NF‐κB p65; (2) 1, 25 – (OH) 2D3 increased the stability of IκBα mRNA with reduced IκBα phosphorylation in asthma serum passively sensitized HASMCs and significantly increased IκBα expression in these HASMCs. Inhibiting NF‐κB signalling with 1, 25 – dihydroxyvitamin D3 may be a therapeutic approach for controlling HASMC‐related remodelling in asthma.